Greener future : building sustainable tourism communities - Jimenez Ruiz, Andrea, 1981-; Rudkouskaya, Volha, 1985-; Bhartiya, Shivam (Emerald Publishing, 2025)
"In Greener Future: Building Sustainable Tourism Communities, a diverse array of contributors addresses the need for innovative and practical solutions for creating sustainable tourism communities. This discerning work delves into the intricate landscape of sustainable tourism development, offering invaluable insights and practical strategies for fostering a symbiotic relationship between travelers, local economies, and cultural preservation efforts. Important topics covered include responsible travel, sustainable tourism, eco-friendly infrastructure, community engagement, and environmental conservation. Contributors draw on real-world examples and best practices to inspire and guide readers in implementing sustainable initiatives within tourism communities. Greener Future will appeal to academics and professionals working in the tourism sector, such as tour operators, destination managers, and hotel managers, who will find vital tips on developing and marketing sustainable tourism projects that benefit both communities and companies."-- Back cover.
Keywords: Ecotourism.; Tourism -- Environmental aspects.; Sustainable development.; Community-based tourism.; elektronické knihy; electronic books